As Testemunhas de Jeová e o Regime Nazista: uma análise das causas ideológicas do conflito - Simões, Marco Antonio (2016)
The objective of this paper is to analyze the confrontation occurred between the German Nazi Party and the religious group Jehovah's Witnesses, called at the time Bibelforschers (Bible Students). The group has positioned itself ideologically against the Nazi Party's proposals, and did so adamantly, that became the subject of an intensity of persecution proportionally higher than the other persecuted religious groups and banned by the regime, as will be shown. The research will examine the emergence and development of the group, emphasizing the establishment of the doctrines that made possible confrontation. Also it will examine the development of Nazi ideology in ways that opposed the position expressed by the group. About the Nazi party, it will still be analyzed as he himself being a religion. The strategies for survival adopted by other groups will also be studied for contextualization purposes. Finally, some illustrative facts of the conflict itself will be presented and analyzed, as a demonstration of the materialization of the ideological conflict. Although Jehovah's Witnesses have been studied in other ways, it is possible to see that the conflict of this group with the Nazi Party has been little studied in Brazil, perhaps because of being a small group in Germany in the period treated by this research. And when mentioned, it is usually under an aspect eminently historic. The purpose of this work is to identify the ideological causes of the conflict